Kompetensi Pedagogik Guru Matematika Sekolah Menengah Pertama Negeri Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Fakhrul Jamal; Cut Morina Zubainur; Anizar Ahmad (Jurnal Peluang, 2019)
Certification is the process of granting certificates to the teacher to determine the feasibility of a teacher in carrying out her/his duties as agents of school learning.  A certificate is provided to educators who have met the requirements of teacher competency test. The results for the West Aceh district showed that it had not reached the standards set by the government. These results did not demonstrate the competence of teachers for each competency. The purpose of this study was to determine the pedagogic competence and professional competence of teachers of mathematics in junior high school Johan Pahlawan sub-district of West Aceh district. Subjects in this study were 11 middle school mathematics teacher at the First State District of Johan Pahalwan West Aceh district. Data were collected through observation and tests. Data were analyzed qualitatively based on indicators of teachers' pedagogical competence and professional competence. The survey results revealed that the pedagogical competence of teachers in preparing lesson plans, implementation of learning and testing were good. Two out of 11 teachers studied had excellent pedagogical competence. In contrast, ten other teachers are still in the category of good, but the test many teachers did not answer the true with an average of fifteen questions that the answer is correct. Professional competence of teachers is still many teachers who are not able to provide answers to the questions given. However, 11 teachers were able to answer very satisfying to items (2), (3), (5), (10) and (11). As for the other as a matter of no one only four teachers who were able to answer correctly, then to question number 10 only three teachers who answered correctly but for a matter that only eight teachers who answered correctly.